2018
DOI: 10.4236/jtr.2018.63021
|View full text |Cite
|
Sign up to set email alerts
|

<i>gyrA</i> Gene Mutation Conferring Phenotypic Cross-Resistance among Fluoroquinolones (Ofloxacin, Levofloxacin and Gatifloxacin) in Multidrug Resistant <i>Mycobacterium tuberculosis</i> Strains Isolated from Pulmonary MDR-TB Patients in Bangladesh

Abstract: Background and objectives: Fluoroquinolones (FLQs) are an essential component of multidrug resistant-tuberculosis (MDR-TB) treatment regimen but unfortunately the emergence of FLQ resistant MDR-TB cases is challenging the current MDR-TB treatment regimen. FLQ resistance is mainly caused by gyrA gene mutation and phenotypic cross-resistance may occur among the different FLQs. A limited number of data exists regarding the cross-resistance phenomenon among FLQs and it appears that resistance to the present class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
3
2
Order By: Relevance
“…The percentage of pre-XDR-TB among MDR-TB isolates was slightly lower than reported in a previous study in Bangladesh ( Tasnim et al., 2018 ). Drug-resistance patterns in MDR-TB isolates may differ due to mutational variability in mycobacterial genes linked with anti-TB drug resistance ( Lan et al., 2019 ).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The percentage of pre-XDR-TB among MDR-TB isolates was slightly lower than reported in a previous study in Bangladesh ( Tasnim et al., 2018 ). Drug-resistance patterns in MDR-TB isolates may differ due to mutational variability in mycobacterial genes linked with anti-TB drug resistance ( Lan et al., 2019 ).…”
Section: Discussioncontrasting
confidence: 76%
“…Our results showed a 3% prevalence of pre-XDR-TB. Compared with our findings, pre-XDR-TB has been found to be more common in India (56%), China (34%), Bangladesh (16%), Pakistan (24%), South Africa (17%), and Nigeria (17%), according to many studies ( Adwani et al., 2016 ; Daniel et al., 2013 ; Mlambo et al., 2008 ; Tasnim et al., 2018 ; Yuan et al., 2012 ). Additionally, a study from India showed higher prevalences of pre-XDR-TB (49.4%) and XDR-TB (11.4%) than our findings ( Singhal et al., 2016 ).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The base T mutation to A in rs17580, which is located in the coding region of the SERPINA1 gene, causes a change in amino acid from glutamate to valine, which alters the entire protein structure and affects the function of the encoding enzyme [ 10 , 11 ]. Studies have found that the occurrence of drug resistance of Mycobacterium tuberculosis is related to mutations of multiple genes [ 12 , 13 ]. A recent study found a high correlation between mutations in the SERPINA1 gene and chronic obstructive pulmonary disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%